Análisis del comportamiento de los actores regulados (beneficiarios directos) durante la implementación de la Política Pública “Canasta Comercial Transfronteriza”, en la Provincia del Carchi - Ecuador periodo 2015 al 2017. - Franco Olivo, María Teresa (2018)
Ecuador has applied tariff surcharges (Special Taxes) in a temporal way, they are urgent measures with the object of regulating imports and care for the equilibrium in payment balance; this component is backed by the national legislation. Due to currency devaluation in neighbor countries, many sectors have been affected, therefore the government has created the “Transborder Commercial Basket of Carchi’s Province”, allowing merchants of this province to acquire products from Colombia and sell them in more competitive prices, leading a commercial activity reactivation. This measure has been applied thru resolution 039-2015 which stablish the procedure to follow for the transborder commercial basket of Carchi province, which begun on October 16, 2015. The following work analyses the behavior of regulated actors which were direct beneficiaries of the public policy “Transborder Commercial Basket of Carchi’s Province” from 2015 to 2017, with the purpose of having a clear vision of which factors allow or impede the successful implementation of such policy. The analysis was made under the case study technique, with a quantified methodology, analyzing the behavior generated by the policy in direct actors that benefitted from “Transborder Commercial Basket of Carchi’s Province”, it was used as well related works with the economic diagnostic and social abilities of Tulcan and Ipiales, with the end of identify how the socio-economic condition influenced said policy.